In Vitro Antimicrobial Effect of a Cold Plasma Jet against Enterococcus faecalis Biofilms. (24th January 2012) - Jiang, Chunqi; Schaudinn, Christoph; Jaramillo, David E.; Webster, Paul; Costerton, J. William
Abstract : The hypothesis that a cold plasma jet has the antimicrobial effect against Enterococcus faecalis biofilms was tested in vitro . 27 hydroxyapatite discs were incubated with E. faecalis for six days to form a monoculture biofilm on the disc surface. The prepared substrata were divided into three groups: the negative control, the positive control (5.25% NaOCl solution), and the plasma treatment group. Resultant colony-forming unit counts were associated with observations of bacterial cell morphology changes using scanning electron microscopy (SEM). Treatment of E. faecalis biofilm with the plasma and 5.25% NaOCl for 5 min resulted in 93.1% and 90.0% kill (P < 0.0001 ), respectively. SEM detected that nearly no intact bacteria were discernible for the plasma-exposed HA disc surfaces. The demonstrated bactericidal effect of the plasma with direct surface contact may be due to the enhanced oxidation by the locally produced reactive plasma species.